Capturing heritage value through innovative mechanisms - Ahmad Shuib,; Nithanan Koshy Mathew, (Institut Alam dan Tamadun Melayu, Universiti Kebangsaan Malaysia, 2016)
Cultural heritage (CH) is a public good which is not traded in the market, thus market fails to indicate the true value of the CH, giving the impression that CH has zero or minimal economic value. Furthermore, the public good nature of CH has made the consumption of most CH to be FOC or at the minimum price; thus the revenues generated from consumption of CH is insufficient to maintain, what more to finance conservation of the CH. Without strong supports from government and public subsidy, the conservation of many important cultural assets are neglected or at best given lip service. People obtain significant benefits from CH in many forms, yet CH is threatened with degradation and destruction. Although several techniques to capture the economic value of the changes in CH, which are external to the market, have been developed but the validity and reliability of the values are often questioned. The present paper will discuss the use of the stated preference approach (CVM) to assess the economic value of CH and to deliberate on the issues and limitation of the approach. New innovative techniques are being further developed that take into account preferences for cultural assets that have wider ranging multifaceted concepts and different motivational concerns.